KEBUTUHAN MAHASISWA PGSD TERHADAP MATA KULIAH BAHASA INGGRIS - Yuyun Yulia (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2017)
Government Regulation No 19 Year 2005 stipulated that the aim of language teaching is  language  competences,  that  is  to communicate.  Basically,  teachers  are  required  to  have  four competences – personal, social, pedagogical and professional – with the two last competences being critical since teachers are considered as language models, particularly in classroom activities. As well,  teachers’ competences  can  drive  students’  motivation  to  learn  over  both  the  short-term  as well as the long-term.This paper aims at describing students needs – necessities, lacks and wants of students in primary school teacher in structuring teaching and learning in class in the Indonesian context.  The  subject  of  the  research  werestudents  in  early  and  late  semester  of  primary  school teacher department (Pendidikan Guru Sekolah Dasar) either in government or private universities in the Yogyakarta province. A survey schedule as well as class observation were used to gather the data. The result shows that English is learnt to develop their teaching professionalism, pursue further study as well as to gain knowledge. In relation to the goal, students need to learn not only to know the language but also to how to teach English in primary schools.